La propagación de material de siembra de calidad para mejorar la salud y productividad del cultivo: prácticas clave para las musaceas: guia ilustrada - Staver, Charles; Lescot, T. (Bioversity International, 2015)
This illustrated guide summarizes the key practices for producing clean planting material of banana with a high yield potential for smallholders, depending on the pests and diseases which are present. The guide is also designed to contribute to better planning of the propagation of planting material for rural development and disaster relief projects.